2016
DOI: 10.1002/fsn3.391
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of proximate composition and sensory attributes of Clariid catfish species of Clarias gariepinus, Heterobranchus bidorsalis, and their hybrids

Abstract: Clariid catfish are favorite food fish especially in African and Asian continents. Recently there has been preference for particular species or hybrids of these species based on quality assurance and value addition. Consequently, this study aimed to evaluate the possible effect of different catfish species and their hybrids on proximate composition and sensory attributes. Catfish species, Clarias gariepinus (CC), Heterobranchus bidorsalis (HH), with their hybrid (CH), and reciprocal hybrid (HC) were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…In turn, the chemical usefulness of the raw material is determined by its chemical composition, losses during storage and thermal treatment, as well as the pH of the meat. Our study showed, as well as the literature data, that African catfish meat has a good nutritional value [ 22 , 23 , 24 ], thus it can replace raw materials and animal products in the human diet. Additionally, the results did not show significant differences in the basic chemical composition or the energy values of heteroclarias and C. gariepinus meat.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In turn, the chemical usefulness of the raw material is determined by its chemical composition, losses during storage and thermal treatment, as well as the pH of the meat. Our study showed, as well as the literature data, that African catfish meat has a good nutritional value [ 22 , 23 , 24 ], thus it can replace raw materials and animal products in the human diet. Additionally, the results did not show significant differences in the basic chemical composition or the energy values of heteroclarias and C. gariepinus meat.…”
Section: Discussionsupporting
confidence: 81%
“…This was also confirmed by the results obtained for this species (16.8–17.42% of protein, and 5.3–5.7% of fat) by Rosa et al [ 22 ], Chwastowska-Siwiecka et al [ 5 ], and Chwastowska-Siwiecka et al [ 27 ]. However, the content of protein (17%) and fat (3%, low-fat species) in the heteroclarias meat was respectively higher and lower than that observed by Olaniyi et al [ 24 ] in the meat of H. bidorsalis (66.8% crude protein—approx. 14.9% protein in d.m., and 21.5% ether extract—approx.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…It has since been distributed and promoted in Germany, Belgium and the Netherlands. In the last decade, the timeconsuming culturing of C. gariepinus has also been propagated in Southeast Asian, including the production of hybrid species (Olaniyi et al, 2017;Rosa et al, 2007). The use of C. gariepinus in Europe is not as widespread, because the weak consumer response limits the effectiveness of promotional campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…The use of C. gariepinus in Europe is not as widespread, because the weak consumer response limits the effectiveness of promotional campaigns. This species is economically important, especially on the African and Asian continents, as its demand and, consequently production, increases continually (Olaniyi et al, 2017). It is popular due to its resistance to disease, fast growth rate and tolerance to low oxygen levels (Wan Norhana et al, 2012) growth performance, short generation interval and consumer preference (Olaniyi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%